A comparison of lepidopteran damage to Hort16A and Hayward kiwifruit - McKenna, C.E.; Stevens, P.S. (New Zealand Plant Protection, 2007)
The timing and incidence of lepidopteran damage to two kiwifruit cultivars Hort16A and Hayward were compared by monitoring tagged fruit bunches on unsprayed vines over two seasons In both seasons the percentage of fruit with caterpillar damage increased rapidly during the 8 weeks immediately after fruit set No new damage was found on Hort16A fruit after this time but Hayward fruit continued to be damaged from February until May Only 74 (both seasons) of Hort16A fruit incurred severe damage (nonexport) compared with 11 7 (1997) or 184 (1998) of Hayward fruit Damage to Hort16A fruit was generally to the sepal area or side of fruit whereas the side of fruit or stamen end were the most common feeding sites on Hayward Ctenopseustis obliquana and Stathmopoda spp caterpillars were the predominant species found on Hort16A fruit while C obliquana and Cnephasia jactatana were the most common species found on Hayward fruit